Association of plasma biomarkers, p‐tau181, glial fibrillary acidic protein, and neurofilament light, with intermediate and long‐term clinical Alzheimer's disease risk: Results from a prospective cohort followed over 17 years. Issue 1 (2nd March 2022) - Stocker, Hannah; Beyer, Léon; Perna, Laura; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Stockmann, Julia; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann
Abstract: Introduction: Blood biomarkers for Alzheimer's disease (AD) are the future of AD risk assessment. The aim of this study was to determine the association between plasma‐measured phosphorylated tau (p‐tau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) levels and risk of clinical AD incidence with consideration to the impact of cardiovascular health. Methods: Within a community‐based cohort, biomarker levels were measured at baseline using single molecule array technology in 768 participants (aged 50–75) followed over 17 years. Associations among biomarkers and AD, vascular dementia, and mixed dementia incidence were assessed. Results: GFAP was associated with clinical AD incidence even more than a decade before diagnosis (9–17 years), while p‐tau181 and NfL were associated with more intermediate AD risk (within 9 years). Significant interaction was detected between cardiovascular health and p‐tau181/NfL. Discussion: GFAP may be an early AD biomarker increasing before p‐tau181 and NfL and the effect modifying role of cardiovascular health should be considered in biomarker risk stratification.